Assessment of geometrical remodelling of the aortic arch after hybrid treatment. (7th December 2018) - Spinella, Giovanni; Finotello, Alice; Conti, Michele; Faggiano, Elena; Gazzola, Valerio; Auricchio, Ferdinando; Chakfé, Nabil; Palombo, Domenico; Pane, Bianca
Abstract: OBJECTIVES: The aim of this study was to measure the morphological remodelling of the ascending aorta, aortic arch and thoracic aorta after aortic arch hybrid treatment including debranching and stent graft implantation. METHODS: Preoperative, 1- month and 1-year follow-up of computed tomography angiography scans of 22 patients were analysed to compute the lumen centreline from the aortic root to the coeliac trunk, and the following measurements were derived: the total centreline length, distance from the aortic root to the left subclavian artery, distance from the left subclavian artery to the distal landing zone. For both pre- and postoperative centrelines, the pointwise curvature was measured at the proximal and the distal landing zones. The mean curvature values of the whole aortic segment and the endografting region of the ascending and the descending aorta were measured. Surface outerline was computed as well, and curvature values at the endograft landing points were extracted. RESULTS: At the 1-month follow-up, centreline length were already significantly increased (382.66 ± 48.69 to 388.1 ± 50.75 mm; P  = 0.01). Centreline pointwise curvature increased in the proximal (+29%, P  = 0.011) and the distal zones (+63%, P  = 0.004). Similarly, pointwise curvature of the outerline significantly increased in the proximal (+77%, P  = 0.01) and the distal landing zones (+100%, P  = 0.04). The centreline mean curvature increased in the ascending aorta (+7%, P  = 0.02) and decreased in the endografting region (−3.3%, P  = 0.004). No evidence of a relationship of such a remodelling with the type of endograft and the type of pathology was observed. This remodelling trend was confirmed by the analysis of 1-year computed tomography angiographies. CONCLUSIONS: Hybrid arch repair was associated with a significant elongation of the vessel and a significant increase in the curvature on the ascending aorta and the descending aorta and on the endograft proximal and the distal landing zones.